Pengaruh Prosedur Kerja, Wewenang, Penilain Prestasi Kerja Dan Evaluasi Kinerja Terhadap Prestasi Kerja Pegawai Sekretariat Daerah Kabupaten Lahat - Ardiansyah, Ardiansyah; Antoni, Darius; Oktala , Rosananda (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aimed to determine and analyze the influence of work procedures, authority, work performance assessment, and performance evaluation individually and together on the work performance of employees of the Lahat Regency Regional Secretariat. The research method used in this study is quantitative, using a questionnaire distributed to respondents. Data quality tests were conducted using validity, reliability, and normality tests. The descriptive and inferential analysis used statistical calculations with multiple regression formulas, partial tests, simultaneous tests, and coefficient of determination. The study results show that work procedures significantly affect the work performance of employees of the Lahat Regency Regional Secretariat. Authority has a significant effect on the work performance of employees of the Lahat Regency Regional Secretariat. Work performance assessment has a significant effect on the work performance of employees of the Lahat Regency Regional Secretariat. Performance evaluation has a significant effect on the work performance of employees of the Lahat Regency Regional Secretariat. Work procedures, authority, work performance assessment, and performance evaluation significantly affect the work performance of the Lahat Regency Regional Secretariat employees